Assessment of subendocardial vs. subepicardial left ventricular twist using tagged MRI images - Tavakoli, Vahid; Sahba, Nima (Cardiovascular Diagnosis and Therapy, 2013)
Objective: The objective of this study is to determine the normal value of 3D left ventricular (LV) twist in subendocardial, mid-wall and subepicardial layers, as well as to study the effects of aging on 3D LV twist by tagged MR motion tracking techniques. Three dimensional motion detection based on 3D tagged MR images is robust to out-of-plane motion error; while 2D motion detection is inherently unable to analyze the 3D cardiac motion and may lead to inaccurate results. Methods: The 3D LV volumetric images were acquired in 52 normal adult subjects (aged 21-82) and were analyzed by using 3D HARmonic phase (HARP) technique. HARP technique provided the 3D displacement fields and the displacements were utilized to compute the rotational values. LV twist was defined as apical rotation relative to the basal rotation, in the 3D coordinates. The LV twist values of subendocardial, midwall and subepicardial layers were analyzed separately. The measured parameters in this study were: peak apical rotation, peak basal rotation, and peak LV twist. Result: Looking at the apex, the normal LV maintains a clockwise rotation in the LV basal plane and a counterclockwise rotation in the LV apical plane. In general, the apical and basal rotation values increase during the aging process, leading to an increased value of LV twist. Peak epicardial LV twist is (10.4±2.6 degrees) which is lower than the mid-wall LV twist (11.3±2.2 degrees) and endocardial LV twist (12.1±2.6 degrees) in the young group (21-35 years old). Also, peak epicardial LV twist is (12.2±2.6 degrees) which is lower than the mid-wall LV twist (14.4±2.8 degrees) and endocardial LV twist (14.7±2.5 degrees) in the middle aged group (21-35 years old). In a similar way, peak epicardial LV twist is (14.8±2.9 degrees) which is lower than the mid-wall LV twist (15.7±3.6 degrees) and endocardial LV twist (16.7±3.0 degrees) in the old group (50-65 years old). Regarding the older group (more than 65 years old), peak epicardial LV twist is (15.9±3.1 degrees) which is lower than the mid-wall LV twist (16.2±3.4 degrees) and endocardial LV twist (18.3±3.0 degrees). Conclusions: It is feasible to measure the subepicardial, mid-wall and subendocardial twist in tagged MR images. The twist value gradually increases in the aging process. Outside layers have greater twist values compared to the inside layers.